2020
DOI: 10.3390/molecules25174009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Potential Haptens with Morphine Skeleton and Determination of Protonation Constants

Abstract: Vaccination could be a promising alternative warfare against drug addiction and abuse. For this purpose, so-called haptens can be used. These molecules alone do not induce the activation of the immune system, this occurs only when they are attached to an immunogenic carrier protein. Hence obtaining a free amino or carboxylic group during the structural transformation is an important part of the synthesis. Namely, these groups can be used to form the requisite peptide bond between the hapten and the carrier pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…We have recently investigated N ‐carboxymethyl opioid compounds, [19] where we showed that the basicity of the carboxylate site is smaller by several orders of magnitude than that of the amino site, thus K 2 values of the dibasic 3‐ O ‐carboxymethyl compounds characterize almost exclusively the protonation of the carboxylate sites, with K 2 practically equal to knormalNC .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently investigated N ‐carboxymethyl opioid compounds, [19] where we showed that the basicity of the carboxylate site is smaller by several orders of magnitude than that of the amino site, thus K 2 values of the dibasic 3‐ O ‐carboxymethyl compounds characterize almost exclusively the protonation of the carboxylate sites, with K 2 practically equal to knormalNC .…”
Section: Resultsmentioning
confidence: 99%
“…Non‐linear parameter fitting with Origin 8 provided the protonation constants from the volume differences [27] . The method of measurements was identical to our previous work [19] …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations